2021
DOI: 10.3389/fonc.2021.633415
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omic Analyses of the m5C Regulator ALYREF Reveal Its Essential Roles in Hepatocellular Carcinoma

Abstract: The ALYREF protein acts as a crucial epigenetic regulator in several cancers. However, the specific expression levels and functional roles of ALYREF in cancers are largely unknown, including for hepatocellular carcinoma (HCC). In a pan-cancer tissue analysis that included HCC, we assessed the expression of ALYREF compared to normal tissues using The Cancer Genome Atlas database. Associations between ALYREF gene expression and the clinical characteristics of HCC patient samples were assessed using the UALCAN da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 47 publications
1
36
0
Order By: Relevance
“…Moreover, increasing evidence has recently proven that RNA modification regulators had the potential to act as the biomarkers for diagnosis and prognostic monitoring in cancer ( 54 56 ). The m5C reader ALYREF expression was dysregulated in several cancers, and higher ALYREF expression was associated with poor prognosis in hepatocellular carcinoma ( 57 ). Some studies indicated that m5C writers NSUN3 and NSUN4 were associated with the infiltration of some immune cells, such as CD8+ T cells and neutrophils ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increasing evidence has recently proven that RNA modification regulators had the potential to act as the biomarkers for diagnosis and prognostic monitoring in cancer ( 54 56 ). The m5C reader ALYREF expression was dysregulated in several cancers, and higher ALYREF expression was associated with poor prognosis in hepatocellular carcinoma ( 57 ). Some studies indicated that m5C writers NSUN3 and NSUN4 were associated with the infiltration of some immune cells, such as CD8+ T cells and neutrophils ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that expression of ALYREF is related to the prognosis of HCC patients through public database analysis [13] . Nevertheless, the mechanism of action of ALYREF in HCC is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“… [8] , [9] , [10] , [11] , [12] . Xue et al [13] have pointed out that ALYREF might be a prognostic factor for HCC. Nevertheless, the specific biological function of ALYREF in HCC and its relationship to the immune system have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, RNA methylation of ncRNAs has gained much attention (50)(51)(52)(53)(54). For instance, M6A, a well-known type of RNA modification at the posttranscriptional level, has been reported to be involved in the expression of miRNAs, circRNAs and lncRNAs in HCC (Table 3 and Figure 1C).…”
Section: Rna Methylationmentioning
confidence: 99%